Pressure drop and flow characteristics in a diffuser with a dimpled tube / Ehan Sabah Shukri Askar and Wirachman Wisnoe - Shukri Askar, Ehan Sabah; Wisnoe, Wirachman (Universiti Teknologi MARA, 2021)
The pressure drops and flow characteristics in a diffuser fitted with a semidimpled tube are numerically studied. Air is selected as a working fluid and its physical properties are modelled using pressure and velocity distribution. The study reveals that every semi-dimple act as a vortex generator. They provide the flow with intensive vortices between the dimpled surface and the diffuser wall. Therefore, they cause an enhancement in the pressure drop inside the diffuser. The performance of the dimples consisting of sphere type dimples with 5 mm in diameter. Three “Reynolds number” operated in the range of 25000 ˂Re˂ 50000 that is based on the hydraulic diameter of the diffuser Dh. The variation in Reynolds number is examined to further investigations of the pressure drop and flow characteristics of the diffuser. The numerical simulations are conducted using incompressible steady-state Reynolds Averaged Navier Stokes equations and the turbulence model “RNG k-e is utilized in the current study. The flow characteristics of the diffuser with semi-dimpled tube are analysed and compared in terms of pressure contour, velocity profile, and velocity vectors, at the operating range of Reynolds numbers. The results are discussed to point out the flow structure mechanisms. It is found that equipping the diffuser with a semi-dimpled tube leads to an increase in the recirculation and vortices inside and near the dimples area. Therefore, they have a considerable influence on the flow field. For the diffuser equipped with a semi-dimpled tube, it is noted that the flow characteristics depend on the Reynolds number. The pressure drop in the flow direction becomes lower with increasing Reynolds number. The findings indicate that for the semi-dimples, increasing Reynolds number increases the velocity distribution significantly due to better mixing of the air.